Long-term culture of Antarctic seaweed, Phyllophora antarctica (Rhodophyta), sampled at Syowa Station - Masao Ohno; Yoshitaka Kondo; Teruo Tobayama; Shigeru Sakakibara; Takao Hoshiai (National Institute of Polar Research, 1999)
Fronds of the Antarctic seaweeds, Phyllophora antarctica and Phycodrys antarctica fronds, attached to sea urchins (Sterechinus neumayeri) caught with a bait-trap, were collected from ice-covered shore of Kita-no-seto Strait near Syowa Station during the 1982 summer. For about three months, Phyll. antarctica fronds were maintained at approximately 0℃ in the refrigerator of the icebreaker FUJI. After April 1982,they were maintained in a glass culture tank at Kamogawa Sea World, Chiba, Japan. Aerated seawater was supplied through a closed re-circulation system; water temperature was kept between -1.9 and 1.5℃ The tank was illuminated with a 10W day-light fluorescent tube (12h light, 12h dark). Phyll. antarctica survived in the tank for 16 years. Producing new growth at the margin of the original fronds, the old parts decayed. Consequently the biomass of fronds increased 20-30 times. It was noted that the biomass increase was greater with the cohabitation of such animals as fish, echinoids, asteroids, gastropods and nemertineans than that when the seaweeds were maintained without animals. In the 1985 summer, fronds of the same Phyll. antarctica were again collected by the same method. The fronds were taken to the Usa Marine Biological Institute, Kochi University, Japan. Those fronds were cultivated in 200ml of enriched seawater with SWII medium in dishes (500ml). The fronds were kept in an incubator 5℃ in fluorescent light ranging from 5-50μE・(cm)^<-2>・s^<-1>(12L/12D). The fronds survived for 3 years under the lower light conditions, but their growth was lower and their size was smaller than the fronds cultured in Kamogawa Sea World. Newly collected fronds were also maintained in dark conditions at 0-5℃ The fronds survived well for one year but then died after de-colarization of fronds after 3 years. We concluded that the survival of Phyll. antarctica was better at 0℃ than at 5℃